Agile Behaviors in Organizations - Szopa, Anna Maria (Archives of Business Research, 2018)
Nowadays enterprises by facing a changeable, turbulent and very competitive environment are testing, implementing and developing new strategies. Even though agility has been widely accepted as an effective management concept, the understanding of how to build and maintain agile workforce still remains undervalued. Presented article provides literature review and empirical evidence of agile behaviors to better understand essential elements of agile workforce and their relationship with organizational agility.